The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/cbin.11664
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNA‐1246 from human umbilical cord mesenchymal stem cells potentiates myocardial angiogenesis in chronic heart failure

Abstract: microRNAs (miRNAs) are of importance to chronic heart failure (CHF). However, the relevance of the exosomal miRNAs produced during CHF remains unknown. Our purpose here was to examine the relevance of exosomal microRNA‐1246 (miR‐1246) released from human umbilical cord mesenchymal stem cell (hucMSC) during CHF and the mechanism of action. Cardiac function, myocardial infarction area, apoptosis, and angiogenesis were all evaluated in a CHF rat model following treatment with hucMSC‐derived exosomes (hucMSC‐Exos)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In addition, CHF is prone to malignant arrhythmias such as ventricular tachycardia and ventricular fibrillation, which leads to an increasing risk of sudden death. With the trend of population aging and the improvement of treatment of coronary heart disease, hypertension, and cardiomyopathy in China, the incidence and medical costs of heart failure are increasing day by day [ 13 15 ]. Although long-term progress has been made in the routine drug treatment of heart failure, the readmission rate and mortality rate of patients with CHF are still very high and do not achieve the expected quality of life [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CHF is prone to malignant arrhythmias such as ventricular tachycardia and ventricular fibrillation, which leads to an increasing risk of sudden death. With the trend of population aging and the improvement of treatment of coronary heart disease, hypertension, and cardiomyopathy in China, the incidence and medical costs of heart failure are increasing day by day [ 13 15 ]. Although long-term progress has been made in the routine drug treatment of heart failure, the readmission rate and mortality rate of patients with CHF are still very high and do not achieve the expected quality of life [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of PRSS23 has been detected in nuclei and extracellular vesicular exosomes where the protease is a component of the human secretome 30 . Exosomal PRSS23 is, e.g., involved in cardiovascular disease where the protease likely mediates Snail/alpha‐smooth muscle actin signalling 31 . In cancer, PRSS23 is implicated in tumor progression, and it was identified in a systematic network survey of a meta-analysis of breast cancer microarray expression data as one of six genes involved in acquired lapatinib resistance 32 .…”
Section: Discussionmentioning
confidence: 99%
“…152 Furthermore, a growing number of studies have shown that progenitor and stem cell-derived exosomal miRNAs, such as miR-31, miR-132, miR-210, miR-322, and miR-1246, present pro-angiogenic activity in cardiac ECs. [153][154][155][156][157] EPC-derived exosomal miR-1246 and miR-1290 reportedly induce the phenotypic shift from FBs to ECs, thus enhancing angiogenesis after MI. 158 Besides, Zhu et al confirmed that macrophage migration inhibitory factor (MIF) enhances the pro-angiogenic effect of MSCs through upregulating exosomal miR-133a-3p.…”
Section: Mirnas In Cardiac Angiogenesismentioning
confidence: 99%